Exploring the influence of teachers’ education and professional development in Cypriot higher education CALL practices - Soule, Maria Victoria; Papadima-Sophocleous, Salomi (My University, 2019)
The present study examines Computer Assisted Language Learning (CALL) practices in the Cypriot Higher Education (HE) system and their relation to teachers' education in CALL and professional development. It involves 28 second language instructors from public and private universities in the Republic of Cyprus. A survey was designed to assess CALL training, CALL training for technology integration, and CALL practices. The analysis of the data reveals a considerable variety in instructors' training, which ranged from in-service training, seminars, conferences, and lectures on CALL or CALL training as part of Master of Arts (MA) or Philosophical Doctorate (PhD) programmes. Despite this variety, the perception of instructors towards the training received for technology integration was generally positive, particularly in terms of its usefulness for the evaluation, selection, and use of computer-based instructional material. However, we found significant differences in their perception towards the effectiveness of training, leading to the creation of computerbased instructional materials. Similarly, differences were found in the frequency of usage of mobile devices, website creators, wikis, and photo-graphic programmes.
Keywords: Teacher education in CALL; Professional development; CALL practices; Cypriot higher education system